CROSS SECTIONAL STUDY : THE RELATIONSHIP BETWEEN HUSBAND SUPPORT AND THE RISK OF DEPRESSION IN PREGNANT WOMEN IN THE THIRD TRIMESTER - Dwina Mastryagung; Ni Nyoman Sri Artina Dewi; Putu Eka Dewi Silayuni (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Mental health issues such as depression and anxiety among pregnant women remain a significant challenge, particularly in the third trimester leading up to delivery. These conditions can negatively impact nutritional intake and fetal growth. Based on the latest Antenatal Care (ANC) program, mental health screening is included in the 12T services implemented at the Bebandem Community Health Center since 2025. This study aims to analyze the relationship between family support and the risk of depression among pregnant women in the third trimester within the service area of the Bebandem Community Health Center. The study employed an analytical, cross-sectional design with a sample size of 124 pregnant women in the third trimester, selected using a combination of stratified random sampling and consecutive sampling, and analyzed using the Chi-Square (χ²) test. The results showed that family support (p=0.665) was associated with the incidence of depression among pregnant women.